PKM Pengembangan dan Pengolahan Produk Buah Naga di Kecamatan Samboja Kabupaten Kutai Kartanegara - Marjan Wahyuni; Fenty Fauziah; Marwati Marwati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Samboja district in Kutai Kartanegara Regency has a fairly good economic potential: dragon fruit cultivation. Dragon fruit farmers in Samboja District, especially members of the women's farmer group in Sei Merdeka Village, face several problems. When they enter the harvest period, dragon fruit is attacked by plant pests. Dragon fruit is only a few and is supplied by middlemen who are also buyers of the dragon fruit harvest. Middlemen buy the dragon fruit at a meager price compared to market prices. On the other hand, farmers cannot sell dragon fruit themselves directly in supermarkets or in traditional markets. This PKM activity will provide training on how to plant dragon fruit, so that plant pests do not attack it to partner members of the women farmer groups and PKK women's groups. This effort can break the dependence of women farmer group members on middlemen. The PKK group of women who became partners in this activity was given knowledge and skills for further dragon fruit cultivation; the results of this cultivation were processed into various commercial food products, such as noodles, jam brownies, jelly, and syrup. The results and outputs of this PKM activity increase the knowledge and skills of members of the women farmer groups and PKK women in processing dragon fruit into various processed food products. It is also hoped that new MSMEs based on processed dragon fruit products will grow